Phonological awareness digital program: a randomized controlled study - Sá, Marta; Sa-Couto, Pedro; Lousada, Marisa (Revista de Investigación en Logopedia, 2022)
The purpose of this study is to analyze the efficacy of the Phonological Awareness Digital Program (PADP) in typically developing preschool children aged 4 to 6 years. A randomized controlled trial was conducted with a total of 49 children assigned to two groups: the experimental group, EG (n=25) and the delayed control group, CG (n=24). Both groups were assessed before and after the implementation of the PADP. A follow-up study for the experimental group was also performed after two months. Outcome measures of phonological awareness skills (task 1: Syllable segmentation task; task 2: Syllable identification task; task3: Syllable omission task; task 4: Onset-rime units segmentation task; task 5: Phoneme segmentation task; task 6: Phoneme blending task) were evaluated at three separate moments. The results showed significant improvement in phonological awareness skills for the EG between the first and the second assessments for all the tasks considered. Between the second and third assessment, the results showed a significant improvement for the CG. The follow-up study also demonstrated the PADP’s efficacy. The PADP has shown to be an effective program in promoting the development of phonological awareness in children. These findings provide evidence for different professionals to use PADP with preschool children.